GLOBAL MIGRATION’S IMPACT AND OPPORTUNITY: PENCAPAIAN EKONOMI INDIA ATAS KEBERHASILAN MENGUBAH BRAIN-DRAIN MENJADI BRAIN-SIRCULATION - Astari, Aliyah (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2024)
India is one of the countries in East Asia that is classified as an underdeveloped country, India has also gone through an era where their country lacked skilled workers which had made India in economic decline as a result of international migration or known as brain drain, a condition where the country loses skilled workers or residents to developed countries with the aim of getting better jobs. However, because of the seriousness of the Indian government in creating regulations and attracting citizens to return to India, India is currently ranked fourth in the list of countries with the fastest economic growth in the world, this condition is known as reversed brain drain or brain gain.